Prospects and challenges regarding biosurfactants in advancing the petroleum industry - Ahluwalia, Ojasvini; Patel, Niketan; Narmeta, Nikhil; Guzman Sanchez, Sandra; Soares Rosado, Alexandre (Frontiers in Bioengineering and Biotechnology, 2026)
As the global population increases, the petroleum industry is experiencing exponential increase in energy demands. However, the petroleum industry faces a myriad of problems concerning production, operation, sustainability, climate change and broader environmental implications. Traditionally, industry has relied on synthetic surfactants to address these challenges. However, owing to their toxicity, nonbiodegradability, and potential ecological leaching, the industry is increasingly shifting toward natural surfactants. Biosurfactants have numerous applications in the petroleum industry as enhanced oil recovery agents, emulsification and demulsification agents, anticorrosive agents, and biocides for sulfate-reducing bacteria. Biosurfactants are proven to be versatile, stable, and valuable biochemical tools capable of modernizing and mitigating challenges in the petroleum industry while promoting sustainability. To realize their potential, future applications and commercialization of biosurfactants require specific research and technological advancement that can increase their production. This review explores the challenges faced by the petroleum industry and the classification, properties, applications, market share, patents, and promising prospects of biosurfactants in various petroleum industry sectors.